2022
DOI: 10.1590/1677-5449.202200272
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the surgical profile of vascular surgery patients at a tertiary hospital in Curitiba, Brazil

Abstract: Background During the COVID-19 pandemic, healthcare services reduced the number of elective procedures performed. Vascular surgery patients are a group at risk of contracting severe forms of the infection, but are also susceptible to complications of their underlying diseases if they do not receive routine care. It is therefore necessary to understand the direct and indirect impacts and consequences of the pandemic on vascular patients. Objectives To assess the impact of 1 year of the pandemic on a vascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The COVID-19 pandemic has negatively impacted lifestyles and health, especially in individuals with long-term conditions, such as those with peripheral artery disease (PAD). (1)(2)(3)(4) Previous studies have reported reduced physical activity levels, increased sedentary behavior, impaired mental health, and decreased walking capacity in PAD patients during the COVID-19 pandemic. (1,(5)(6)(7) Studies have shown that women suffer more consequences related to PAD than men, presenting with worse functional capacity, impaired vascular function, and higher levels of inflammatory markers and morbidity.…”
Section: ❚ Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has negatively impacted lifestyles and health, especially in individuals with long-term conditions, such as those with peripheral artery disease (PAD). (1)(2)(3)(4) Previous studies have reported reduced physical activity levels, increased sedentary behavior, impaired mental health, and decreased walking capacity in PAD patients during the COVID-19 pandemic. (1,(5)(6)(7) Studies have shown that women suffer more consequences related to PAD than men, presenting with worse functional capacity, impaired vascular function, and higher levels of inflammatory markers and morbidity.…”
Section: ❚ Introductionmentioning
confidence: 99%